Green Synthesis and Characterization of Silver – Cadmium (Ag-Cd Bimetallic Nanopar-ticles From Ocimum Gratissimum Leaves Extract and Evaluation of it Antimicrobial Ac-tivities - Lamayi Danbature , Wilson; Yahaya Pindiga , Nasiru; Lawan , Markus (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Suitable and effective antimicrobial agent bimetallic silver-cadmium nanoparticles was prepared via reduction process using phytochemicals present in Ocimum gratissimum leaves extract as eco-friendly solvents, non-toxic reducing reagents, biodegradable capping and stabilizing agents; characterized by UV-Vis., FTIR, XRD and SEM techniques, and antimicrobial activities were tested on H-pylori, K-pneumonia, S-Typhi, S-Aureus; Aspergillus Niger, and Candida albican. The UV-visible spectroscopic technique confirmed the formation of synthesized nanoparticles with plasma resonance peaks at 600nm for Ag-Cd bimetallic nanoparticles. SEM analysis revealed that Ag-Cd bimetallic nanoparticles, are merely spherical in form; FTIR analysis confirmed the presence of carbonyl, alcoholic groups, unsaturation due to both aliphatic and cyclic (ring) aromatic, metal linkage, aromatic amine and alkyl halides. The XRD analysis indicated Ag-Cd, bimetallic nanoparticles is a Face Centered Cubic (FCC) structure with average crystalline size of 53.82nm. The antimicrobial evaluation results showed an increase in the bacteria’s and fungal growth inhibition with increase in concentration of the bimetallic nanoparticles with inhibition highest at 500ug/ml and 150ug/ml respectively. It could be concluded that the synthesized Ag – Cd could serve as an effective microbial inhibitors.